Propiedades psicométricas de la escala de depresión para adolescentes de Reynolds – segunda versión (EDAR-2) en estudiantes de secundaria de Lima Metropolitana - Pascual Rivera, Jorge Vidal (2022)
Depression is one of the most common mental illnesses in the adolescent population, with an estimated prevalence worldwide of around 8%; however, it is estimated that around 50% experience some symptoms of the depressive spectrum. Due to these circumstances, the present study aimed to validity the psychometric properties of the Reynolds adolescents depression scale (RADS-2), in order to be able to provide new and relevant information in this scenario. The design was non-experimental, being descriptive and cross-sectional, working with a sample of 941 high school students from Metropolitan Lima. Was used the Reynolds adolescents depression scale (RADS 2) adapted to our context. A confirmatory factor analysis was performed to examine the proposed Reynolds structures; considering the average variance extracted (AVE), and the composite reliability (CR). The results indicated that the scores in the new version of the RADS showed acceptable indices and a better fit for this population (¿² (gl) = 1282.89 (269); CFI = .961; TLI = .956; RMSEA = .063 (.060) - .067); SRMR = .045; WRMR = 1.477). Reliability estimates, using the internal consistency method, showed an acceptable range for all the RADS-2 dimensions. These findings supported the validity and reliability of the new version of the Reynolds Adolescent Depression Scale as a measure of depression was acceptable and suggest that it is can be used to evaluate the construct in different studies.